2017
DOI: 10.1093/nar/gkx201
|View full text |Cite
|
Sign up to set email alerts
|

Yeast Sub1 and human PC4 are G-quadruplex binding proteins that suppress genome instability at co-transcriptionally formed G4 DNA

Abstract: G-quadruplex or G4 DNA is a non-B secondary DNA structure consisting of a stacked array of guanine-quartets that can disrupt critical cellular functions such as replication and transcription. When sequences that can adopt Non-B structures including G4 DNA are located within actively transcribed genes, the reshaping of DNA topology necessary for transcription process stimulates secondary structure-formation thereby amplifying the potential for genome instability. Using a reporter assay designed to study G4-indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 56 publications
1
38
0
Order By: Relevance
“…Alternatively, the observed effect could be due to the sequestering and reduced function of Top1-interacting proteins. As further confirmation that Top1 reduces the adverse effect of G4 DNA, loss of Top1 significantly increases sensitivity of yeast cells to the G4-stabilizing ligand TmPyP4 [53]. Defining how the G4 binding properties of Top1 affect genome instability is an important area of future study.…”
Section: Top1 As a Regulator Of Genome Stabilitymentioning
confidence: 98%
“…Alternatively, the observed effect could be due to the sequestering and reduced function of Top1-interacting proteins. As further confirmation that Top1 reduces the adverse effect of G4 DNA, loss of Top1 significantly increases sensitivity of yeast cells to the G4-stabilizing ligand TmPyP4 [53]. Defining how the G4 binding properties of Top1 affect genome instability is an important area of future study.…”
Section: Top1 As a Regulator Of Genome Stabilitymentioning
confidence: 98%
“…For Chromatin IP (ChIP), a previously described protocol was used [34] with following modifications. Anti-FLAG antibody (clone M2 -Sigma) conjugated to Protein G Dynabeads (Life Technologies) were used in pull-down.…”
Section: Chromatin Immunoprecipitationmentioning
confidence: 99%
“…A defective BLM helicase failed to unwind G4-DNA and caused increasing recombination frequencies and a high incidence of cancer in Bloom's syndrome [33]. More recently, the co-transcriptional activator Sub1, which interacts with both G4 DNA and the G4-helicase Pif1, was shown to suppress the G4-associated genome instability by facilitating the recruitment of Pif1 helicase to co-transcriptionally formed G4 DNA structures [34].…”
Section: Introductionmentioning
confidence: 99%
“…ScPif1 interacts physically with Rim1, the yeast mitochondrial ssDNA binding protein, and this interaction increases the product formation for dsDNA unwinding [28]. ScPif1 also interacts with Sub1 [109], a co-transcriptional activator that reduces genome instability at G4DNA sequences in yeast [109]. Sub1 binds tightly to G4DNA but does not unfold G4DNA structures [110].…”
Section: Unanswered Questionsmentioning
confidence: 99%
“…This suggests that Sub1 may instead recruit a G4DNA resolving protein to the G4DNA site. Indeed, Sub1 and ScPif1 interact physically and genetic experiments confirmed that Sub1 and ScPif1 act in the same pathway to suppress G4DNA associated genome instability [109]. ScPif1 has also been shown to interact functionally with Polδ-PCNA through a physical interaction with PCNA [15].…”
Section: Unanswered Questionsmentioning
confidence: 99%